2009
DOI: 10.1007/s11661-008-9760-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Amount of Binder Removal Required during Solvent Debinding of Powder-Injection-Molded Compacts

Abstract: Unsatisfactory dimensional control, distortion, and defects are frequently observed in powderinjection-molded parts, particularly after the solvent and thermal-debinding processing steps. One of the reasons is that the amount of soluble binder removed during the first step, solvent debinding, is not great enough to form interconnected pores throughout the compact, particularly in the core region. Thus, blistering, cracking, and bubbles can form easily during the subsequent thermal debinding. To determine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…When more than 40% of total binder (equivalent to 65% of PEG in this research, shown by the line in the Fig. ) was leached, the connected pore nets were created in the compacts . At this stage, the green body could be moved to the second step of rapid thermal debinding.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When more than 40% of total binder (equivalent to 65% of PEG in this research, shown by the line in the Fig. ) was leached, the connected pore nets were created in the compacts . At this stage, the green body could be moved to the second step of rapid thermal debinding.…”
Section: Resultsmentioning
confidence: 96%
“…8) was leached, the connected pore nets were created in the compacts. 31,32 At this stage, the green body could be moved to the second step of rapid thermal debinding. As connected pore nets formed, gas from thermal degradation of the rest binder could escape from these pore nets easily without cracking or blistering.…”
Section: Debinding Rate Of Large-sized Partmentioning
confidence: 99%
“…As the mass loss of every sample was at least 96 wt% of the wax weight introduced in the blends, we concluded that wax network was highly continuous in the whole sample. Its extraction created an open-pores network characteristic of the sample structure [ 20 ]. The latter reflects binder–binder and particle–binder interactions developed in each blend and can be characterized by porosimetry.…”
Section: Methodsmentioning
confidence: 99%
“…Literatürde de parça kalınlığındaki artışının kimyasal bağlayıcı ayrıştırma süresini arttırdığı belirtilmiştir. Fan ve arkadaşları çalışmalarında numune kalınlığının 2 mm den 8 mm ye çıkması bağlayıcı ayırma süresini 0,8 saatten 12,9 saate çıkardığı tespit etmişlerdir [20]. Ayrıca Oliveira ve Chen çalışmalarında parça kalınlığının bağlayıcı ayırma sürecinde ağırlık kaybına etkisinin olduğunu tespit etmişlerdir.…”
Section: Numune Hacminin Ve Kalınlığının Ağırlık Kaybına Etkisiunclassified